Evolving Paths: Undergraduate Design Education through Graduate and Generative Research with a Particular Focus on Sustainability. (3rd July 2016) - Doğan, Çağla; Turhan, Senem; Bakırlıoğlu, Yekta
Abstract: Design considerations that take into account the diverse issues of sustainability have become a central source of inspiration for third-year design students in the Department of Industrial Design at Middle East Technical University. These considerations include the development of products that can evolve in line with local needs, product maintenance, repair and upgrade, and the effective use of resources and have been integrated into various design projects relating to diverse product sectors (e.g. small household appliances, bathroom tiles and accessories). While engaged in these projects, the graduate students focused on and developed a generative design research method and an innovative idea generation tool that helped the design students better understand and incorporate these considerations into the idea generation phase of the design process. This paper presents suggestions for and insights into the means of bringing together undergraduate education and graduate research by providing examples from design education cases.